Quantitative evaluation of LiPF6 as corrosion inhibiting additive for Al in LiTFSI-based battery electrolytes – An on-line mass spectrometric study - Christopher Behling; Janik Lüchtefeld; Karl J.J. Mayrhofer; Balázs B. Berkes (Electrochemistry Communications, 2024)
Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) is a promising candidate for future lithium-ion battery (LIB) electrolytes because of its increased stability and ionic conductivity. One major drawback of this salt, however, is its ability to dissolve Al, leading to a degradation of current collectors in LIBs over time. Surface passivating additives can reduce or even completely suppress the dissolution. A truly cost and material-efficient suppression, however, can only be achieved by identifying the ideal (i.e., minimal) amount of additive. Therefore, quantifying the dissolution-suppressing effect of additives is necessary to create an optimum electrolyte mixture. In this work, we examine the influence of lithium hexafluorophosphate (LiPF6) addition to LiTFSI-based electrolytes via cyclic voltammetry (CV) in an electroanalytical flow cell (EFC) coupled on-line to an inductively coupled plasma mass spectrometer (ICP-MS) for continuous downstream elemental analysis. This setup allows the potential resolved quantification of Al dissolution with unprecedented precision in real-time. With that, we found that already very small amounts of 0.02 M LiPF6 added to 0.98 M LiTFSI will drastically reduce the total dissolved amount of Al during one CV cycle by a factor of ∼ 20, while electrolytes containing 0.30 M LiPF6 (and 0.70 M LiTFSI) completely suppress the dissolution of Al. These findings allow the substitution of large portions of LiPF6, enabling the production of safer LIBs without risking current collector degradation.